A 12Cr2Mo1V steel forging for pressure vessel and its heat treatment process

By adding a composite cladding layer of tungsten carbide, chromium carbide, titanium or nickel to the surface of 12Cr2Mo1V steel forgings, and combining with heat treatment technology, the problems of insufficient wear resistance, corrosion and insufficient bonding strength in high-temperature and high-pressure environments are solved. It achieves the improvement of the overall performance of the material and the extension of the service life.

CN118835238BActive Publication Date: 2025-02-25JIANGYIN HENGRUN HEAVY IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410895852.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-02-25
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

Traditional 12Cr2Mo1V steel forgings have problems such as insufficient wear resistance, corrosion problems and insufficient bonding strength in high-temperature and high-pressure environments, which are difficult to meet the requirements of long-term and stable use.

Method used

Using a composite cladding layer composed of tungsten carbide, chromium carbide and 5%-10% titanium or nickel, combined with heat treatment technology, including preliminary heat treatment, normalization or quenching treatment and multiple tempering treatments, optimize the microstructure of forgings and The bonding interface between the cladding layer and the substrate.

Benefits of technology

It significantly improves the wear resistance, corrosion resistance and bonding strength of the forgings, extends the service life, and adapts to efficient operation in high-temperature and high-pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118835238B_ABST
    Figure CN118835238B_ABST
Patent Text Reader

Abstract

The present application relates to the fields of materials science and metal processing, and discloses a 12Cr2Mo1V steel forging for a pressure vessel and a heat treatment process thereof, wherein the surface of the steel forging has a composite cladding layer, and the composite cladding layer is composed of tungsten carbide, chromium carbide and 5%-10% titanium or nickel. The heat treatment process comprises the following steps: after the composite cladding layer is prepared, a preliminary heat treatment is performed, the tempering temperature is 250-350°C, and the duration is 2-3 hours; normalizing or quenching treatment is performed, the normalizing temperature is 900-950°C, and the quenching temperature is 930-980°C; after normalizing or quenching, tempering treatment is performed, the tempering temperature is 500-650°C, and tempering is performed at least twice. The present invention provides an efficient and reliable processing method, which greatly improves the comprehensive performance of 12Cr2Mo1V steel forgings, and is particularly suitable for industrial applications requiring extremely high durability and reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material science and metal processing technology, in particular to a 12Cr2Mo1V steel forging for a pressure vessel and a heat treatment process thereof. Background Art

[0002] 12Cr2Mo1V steel, as a widely used chromium-molybdenum alloy steel, is often used to manufacture forgings in high temperature and high pressure environments, such as power station boilers, petrochemical reactors and pressure vessels, due to its excellent high temperature strength and good corrosion resistance. This material needs to have extremely high wear resistance, corrosion resistance and structural stability in a long-term high temperature and high pressure working environment.

[0003] However, traditional 12Cr2Mo1V steel often faces several key problems in practical applications:

[0004] Insufficient wear resistance: Under conditions of high-speed operation and high load, the surface of the material is prone to wear, affecting the normal operation and service life of the equipment.

[0005] Corrosion problem: Although 12Cr2Mo1V steel has certain corrosion resistance, it is still susceptible to corrosion in certain chemical environments, especially under high temperature conditions.

[0006] Bonding strength: In cases where an additional cladding layer is required to improve surface performance, the bonding strength between the cladding layer and the substrate is often difficult to meet the requirements of long-term stable use.

[0007] To solve the above problems, researchers and engineers have carried out a series of technical developments:

[0008] Surface treatment technology: such as thermal spraying, chemical vapor deposition (CVD), physical vapor deposition (PVD), etc., to improve the surface properties of materials and increase wear resistance and corrosion resistance.

[0009] Improvement of heat treatment process: By optimizing heat treatment steps such as normalizing, quenching and tempering, the overall mechanical properties and service life of the material can be improved.

[0010] Although these methods have improved material properties to a certain extent, they usually only involve improvements in a single property and lack a comprehensive solution to simultaneously improve wear resistance, corrosion resistance and bonding strength. In addition, these treatment processes are often complicated and costly, and have high requirements for the operating environment and equipment, which limits their widespread application. Summary of the invention

[0011] In view of the deficiencies in the prior art, the present invention provides a 12Cr2Mo1V steel forging for a pressure vessel and a heat treatment process thereof, which solves the problem that the traditional improvement of 12Cr2Mo1V steel is only aimed at a single performance and is difficult to meet the use requirements.

[0012] To achieve the above objectives, the present invention is implemented through the following technical scheme: a 12Cr2Mo1V steel forging for a pressure vessel, the surface of the steel forging having a composite cladding layer, the composite cladding layer consisting of tungsten carbide, chromium carbide and 5%-10% titanium or nickel.

[0013] Preferably, the particle size of the composite powder is 20-50 microns.

[0014] Preferably, the overlap rate between layers of the composite cladding layer is 40%-60%.

[0015] Preferably, the method for preparing the composite cladding layer comprises the following steps:

[0016] 1) Surface pretreatment, including cleaning and roughening;

[0017] 2) Using laser surface cladding technology to form a composite cladding layer on the surface of the forging, the laser power is 1.5-2.5 kilowatts, and the scanning speed is 800-1200 mm / min.

[0018] Preferably, the roughening treatment in the surface pretreatment is completed by sandblasting or laser grinding, and the surface roughness is Ra 3.2-6.3 microns.

[0019] The present invention also provides a heat treatment process for a 12Cr2Mo1V steel forging for a pressure vessel, comprising the following steps:

[0020] After the composite cladding layer is prepared, it is subjected to preliminary heat treatment, with the tempering temperature at 250-350°C and the duration being 2-3 hours;

[0021] Normalizing or quenching treatment, the normalizing temperature is 900-950℃, and the quenching temperature is 930-980℃;

[0022] After normalizing or quenching, tempering is carried out at a temperature of 500-650°C, and tempering is carried out at least twice.

[0023] Preferably, after the preliminary heat treatment, cooling is performed at a cooling rate of 10-20° C. / min.

[0024] Preferably, the normalizing or tempering treatment after quenching lasts for 1-2 hours each time.

[0025] The present invention provides a 12Cr2Mo1V steel forging for a pressure vessel and a heat treatment process thereof. The following beneficial effects are achieved:

[0026] 1. The present invention significantly enhances the wear resistance of the material by adding a cladding layer composed of tungsten carbide, chromium carbide and titanium or nickel on the surface of the forging. This cladding layer provides additional wear protection, reduces the wear rate of the material under high-load working conditions, and thus extends the service life of the forging.

[0027] 2. The cladding layer combined with the heat treatment process of the present invention optimizes the microstructure of the steel forging and enhances its hardness. This enables the forging to withstand higher working pressures and more severe working conditions, which is particularly important for critical applications such as pressure vessels.

[0028] 3. The present invention optimizes the bonding interface between the cladding layer and the substrate through heat treatment, significantly improving the bonding strength between the cladding layer and the substrate. This enhanced bonding ensures the stability and reliability of the cladding layer in long-term operation and avoids the problem of interlayer peeling.

[0029] 4. The present invention provides an efficient and reliable treatment method, which greatly improves the comprehensive performance of 12Cr2Mo1V steel forgings, and is particularly suitable for industrial applications requiring extremely high durability and reliability. This method not only optimizes the mechanical and chemical properties of the material, but also significantly extends the service life and improves the performance of the product through a coordinated cladding and heat treatment process, ensuring efficient operation in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Please refer to the attached Figure 1 The embodiment of the present invention provides a 12Cr2Mo1V steel forging for a pressure vessel and a heat treatment process thereof, aiming to significantly improve the surface wear resistance, corrosion resistance and overall mechanical properties of the forging by combining innovative laser surface cladding technology with sophisticated heat treatment technology, so as to adapt to harsh working conditions such as high temperature and high pressure.

[0033] 1. Composite cladding layer

[0034] The forging surface of the present invention adopts a composite cladding layer composed of tungsten carbide (WC), chromium carbide (CrC) and 5%-10% titanium (Ti) or nickel (Ni). These materials are selected based on their excellent physical and chemical properties:

[0035] Tungsten carbide and chromium carbide: provide extremely high hardness and wear resistance, suitable for use in environments with high friction and impact loads.

[0036] Titanium and nickel: As binders, they help to improve the bonding strength between the cladding layer and the substrate, and improve the stability and corrosion resistance of the cladding layer at high temperatures.

[0037] The particle size of the composite powder is controlled at 20-50 microns to ensure that it can be evenly melted and form a dense protective layer during the laser cladding process. The overlap rate between the cladding layers is 40%-60% to ensure seamless coverage and avoid the appearance of weak links.

[0038] 2. Laser surface cladding technology

[0039] Laser surface cladding technology uses 1.5-2.5 kilowatts of laser power and 800-1200 mm / min scanning speed. This parameter setting helps to accurately control the formation of the cladding layer while avoiding excessive thermal impact on the substrate. In addition, surface pretreatment (roughening) by sandblasting or laser grinding technology adjusts the surface roughness to Ra 3.2-6.3 microns, increases the mechanical bite between the cladding material and the substrate, and further enhances the adhesion of the cladding layer.

[0040] 3. Heat treatment process

[0041] After the cladding layer is prepared, the forging undergoes preliminary low-temperature heat treatment (250-350°C, 2-3 hours), which helps release the stress generated during the cladding process, prevents the generation of cracks, and promotes the chemical bonding of titanium or nickel with carbides. Next, the forging undergoes normalizing or quenching treatment, with the normalizing temperature set at 900-950°C and the quenching temperature set at 930-980°C. These high-temperature treatment steps optimize the microstructure of the forging and improve its overall mechanical properties.

[0042] Tempering after normalizing or quenching is carried out at 500-650℃, each time lasting 1-2 hours, and at least twice to balance hardness and toughness and ultimately achieve optimal mechanical properties. Through this heat treatment process, not only the mechanical properties of the substrate are improved, but also the performance of the cladding layer is optimized, especially in improving the bonding strength and temperature resistance of the cladding layer.

[0043] The composite cladding layer of the present invention significantly improves the surface hardness of the forging (reaching or exceeding HV 600) and provides long-term protection in high wear and high corrosion environments. The addition of titanium or nickel significantly improves the bonding strength between the cladding layer and the base metal, and the bonding strength can reach 50-100MPa as verified by standard tensile tests or peel tests. The heat treatment process optimizes the overall microstructure of the forging, especially the TiC or NiWC micron-sized particles formed in the cladding layer, which improves its heat resistance and crack resistance.

[0044] In summary, the forging and heat treatment process thereof of the present invention provide a high-performance material solution for pressure vessels, and are particularly suitable for industrial applications requiring extremely high wear resistance and corrosion resistance.

[0045] In order to better understand the present invention, the above method is described in detail below in conjunction with specific embodiments.

[0046] Example 1: Basic titanium enhanced cladding

[0047] Cladding layer preparation

[0048] 1. Material configuration:

[0049] Tungsten carbide (WC): 70%

[0050] Chromium carbide (CrC): 25%

[0051] Titanium (Ti): 5%

[0052] Powder particle size: 30 microns

[0053] 2. Surface pretreatment:

[0054] Surface roughening: sandblasting, roughness Ra 4.0 microns.

[0055] Clean to remove surface impurities.

[0056] 3. Laser cladding:

[0057] Laser power: 2.0 kW.

[0058] Scanning speed: 1000 mm / min.

[0059] Overlap rate: 50%.

[0060] Heat treatment process

[0061] Preliminary heat treatment: tempering temperature 320℃, lasting 2 hours.

[0062] Normalizing temperature: 920℃.

[0063] Quenching temperature: 950℃.

[0064] Tempering: twice, temperature 550℃, each time lasting 1.5 hours.

[0065] Example 2: High nickel content cladding

[0066] Cladding layer preparation

[0067] 1. Material configuration:

[0068] Tungsten carbide (WC): 65%

[0069] Chromium carbide (CrC): 20%

[0070] Nickel (Ni): 15%

[0071] Powder particle size: 40 microns

[0072] 2. Surface pretreatment:

[0073] Laser polished, roughness Ra 3.2 microns.

[0074] 3. Laser cladding:

[0075] Laser power: 2.2 kW.

[0076] Scanning speed: 1100 mm / min.

[0077] Overlap rate: 40%.

[0078] Heat treatment process

[0079] Preliminary heat treatment: tempering temperature 340℃, duration 3 hours.

[0080] Normalizing temperature: 930℃.

[0081] Quenching temperature: 960℃.

[0082] Tempering: twice, temperature 600℃, each time lasting 2 hours.

[0083] Example 3: Low-grain titanium reinforced cladding

[0084] Cladding layer preparation

[0085] 1. Material configuration:

[0086] Tungsten carbide (WC): 60%

[0087] Chromium carbide (CrC): 35%

[0088] Titanium (Ti): 5%

[0089] Powder particle size: 20 microns

[0090] 2. Surface pretreatment:

[0091] Sandblasted, roughness Ra 5.0 microns.

[0092] 3. Laser cladding:

[0093] Laser power: 1.5 kW.

[0094] Scanning speed: 1200 mm / min.

[0095] Overlap rate: 60%.

[0096] Heat treatment process

[0097] Preliminary heat treatment: tempering temperature 275℃, duration 2.5 hours. Normalizing temperature: 910℃.

[0098] Quenching temperature: 940℃.

[0099] Tempering: twice, temperature 525℃, each time lasting 1 hour.

[0100] Example 4: High titanium content cladding

[0101] Cladding layer preparation

[0102] 1. Material configuration:

[0103] Tungsten carbide (WC): 55%

[0104] Chromium carbide (CrC): 30%

[0105] Titanium (Ti): 15%

[0106] Powder particle size: 35 microns

[0107] 2. Surface pretreatment:

[0108] Laser polished, roughness Ra 6.0 microns.

[0109] 3. Laser cladding:

[0110] Laser power: 2.5 kW.

[0111] Scanning speed: 900 mm / min.

[0112] Overlap rate: 45%.

[0113] Heat treatment process

[0114] Preliminary heat treatment: tempering temperature 350℃, duration 3 hours. Normalizing temperature: 940℃.

[0115] Quenching temperature: 980℃.

[0116] Tempering: twice, temperature 650℃, each time lasting 2 hours.

[0117] Example 5: Balanced Titanium-Ni Cladding

[0118] Cladding layer preparation

[0119] 1. Material configuration:

[0120] Tungsten carbide (WC): 50%

[0121] Chromium carbide (CrC): 40%

[0122] Titanium (Ti): 5%

[0123] Nickel (Ni): 5%

[0124] Powder particle size: 25 microns

[0125] 2. Surface pretreatment:

[0126] Sandblasted, roughness Ra 5.5 microns.

[0127] 3. Laser cladding:

[0128] Laser power: 1.8 kW.

[0129] Scanning speed: 950 mm / min.

[0130] Overlap rate: 50%.

[0131] Heat treatment process

[0132] Preliminary heat treatment: tempering temperature 280℃, lasting 2 hours.

[0133] Normalizing temperature is 900℃.

[0134] Quenching temperature 930℃.

[0135] Tempering: twice tempering, temperature 525℃, each time lasting 1.5 hours.

[0136] Test experiment 1:

[0137] Experimental purpose: To evaluate the effects of different cladding material ratios and heat treatment processes on the hardness of the cladding layer of 12Cr2Mo1V steel forgings.

[0138] Experimental materials: Forging samples of Examples 1-5, cladding layer materials and processing parameters are as described above.

[0139] Experimental steps:

[0140] 1. Sample preparation: Cut a test sample of the same size from each example. Make sure the sample surface is flat and has no obvious defects.

[0141] 2. Sample cleaning: Use alcohol and soft cloth to clean the sample surface to remove possible oil and dust.

[0142] 3. Preparation of hardness test instrument: Use Vickers hardness tester.

[0143] 4. Hardness measurement: Measure the hardness of at least five different points on the cladding layer of each sample. Keep the test points at least 1 cm apart to avoid mutual influence. Record the hardness value of each point.

[0144] The experimental results are shown in Table 1:

[0145] Table 1 Vickers hardness test results of 12Cr2Mo1V steel forgings of Examples 1-5

[0146]

[0147] From the data in Table 1, we can get:

[0148] Example 4 shows the highest average hardness value, reaching 646 HV, which is attributed to the use of a higher ratio of titanium and nickel, providing better hardness performance.

[0149] The hardness of Example 3 is relatively low, with an average value of 606 HV, which is due to the decrease in hardness caused by the lower carbide content and smaller particle size.

[0150] The hardness values ​​of other embodiments show that different cladding material ratios and particle sizes have a significant effect on the hardness. Appropriate cladding materials and heat treatment processes can effectively improve the hardness to meet the high performance requirements of pressure vessels.

[0151] Test experiment 2:

[0152] The purpose of the experiment is to evaluate the wear resistance of different cladding layer embodiments under simulated actual use conditions to ensure that the cladding layer of the 12Cr2Mo1V steel forging can resist the wear in the working environment of the pressure vessel.

[0153] Experimental materials: forging samples of Examples 1-5, cladding material ratios and processing parameters are as described above.

[0154] 1. Sample preparation: Cut a standard size sample from each example. Make sure the cladding surface of each sample is smooth and clean.

[0155] 2. Wear test device preparation: Use a ball-on-disc wear tester and set standardized wear load and speed.

[0156] 3. Wear test execution: Each specimen is tested under the same conditions. Set the wear environment: dry or wet grinding conditions, select according to the expected use environment. Record the sample weight before and after the test.

[0157] The test results are shown in Table 2:

[0158] Table 2 Wear resistance test results of cladding layer of 12Cr2Mo1V steel forgings of Examples 1-5

[0159] Example Weight before wear (g) Weight after wear (g) Weight difference (mg) Weight difference (%) Example 1 50.012 49.987 25 0.05 Example 2 50.015 49.98 35 0.07 Example 3 50.008 49.992 16 0.032 Example 4 50.01 49.965 45 0.09 Example 5 50.007 49.985 22 0.044

[0160] From the data in Table 2, we can get:

[0161] Example 3 shows the lowest weight difference and weight difference ratio, indicating that its cladding layer has the best wear resistance. This is due to the enhanced wear resistance provided by its finer powder particle size and high chromium carbide content.

[0162] The wear rate of Example 4 is the highest, which is due to the poor wear performance under dry grinding conditions due to the high titanium content in its cladding layer.

[0163] The wear resistance of other embodiments is between the above two, which shows the influence of different cladding material ratios on wear resistance.

[0164] Test experiment 3:

[0165] Experimental purpose: To evaluate the bonding strength between the cladding layer and the substrate of 12Cr2Mo1V steel forgings under different embodiments, so as to ensure the stability and durability of the cladding layer in a high-pressure working environment.

[0166] Experimental materials: Forging samples from Examples 1-5, cladding material proportions and processing parameters are as described above.

[0167] Experimental procedures

[0168] 1. Sample preparation: Cut test strips of the same size from each example to ensure complete coverage of the cladding layer. Sample dimensions: 100 mm in length, 25 mm in width, and 5 mm in thickness.

[0169] 2. Sample cleaning: Use alcohol and soft cloth to clean the sample thoroughly, making sure it is free of grease and dust.

[0170] 3. Bond strength test instrument preparation: Use a universal material testing machine (UTM) to perform the peel test.

[0171] 4. Bonding strength measurement: Fix one end of the sample and apply tension to the other end through UTM until the cladding layer separates from the substrate. Record the maximum tension value required.

[0172] The experimental data are shown in Table 3:

[0173] Table 3 Peel strength test results of cladding layer and substrate of 12Cr2Mo1V steel forgings of Examples 1-5

[0174]

[0175] From the data in Table 3, we can get:

[0176] Example 4 shows the highest average peel strength, reaching 95.3 N / mm, indicating that the cladding layer has a very strong bond with the substrate, which is due to the high proportion of titanium and nickel working together to enhance the bonding between the metals.

[0177] Example 5 exhibits the lowest bonding strength, averaging 67.7 N / mm, which is due to the lower binder content or the unsatisfactory parameter settings during the cladding process.

[0178] The other examples exhibited moderate levels of peel strength, demonstrating the significant impact of different cladding material ratios on bonding strength.

[0179] Comparative experiment:

[0180] Experimental purpose: To compare the comprehensive treatment effect (cladding and heating treatment) of Example 1 with the performance of single treatment (cladding only or heat treatment only) and untreated 12Cr2Mo1V steel forgings, so as to demonstrate the advantages of the synergistic effect of the present invention in improving material properties.

[0181] Experimental groups:

[0182] Experimental group: Example 1 (cladding + heat treatment)

[0183] Control group 1: 12Cr2Mo1V steel forgings with cladding only

[0184] Control group 2: 12Cr2Mo1V steel forgings subjected to heat treatment only

[0185] Control group 3: 12Cr2Mo1V steel forgings without any treatment

[0186] Experimental setup and steps

[0187] 1. Hardness test

[0188] Experimental procedures

[0189] Sample preparation: Prepare three test samples per group, ensuring consistent size and surface treatment.

[0190] Hardness Test: The hardness was measured at five different points on each sample using a Vickers hardness tester.

[0191] Data recording: record the hardness value of each point and calculate the average hardness.

[0192] 2. Wear resistance test

[0193] Experimental procedures

[0194] Sample preparation: Three samples were selected from each group for abrasion resistance testing.

[0195] Wear test: Use a ball-on-disc wear tester and set the same wear conditions for testing.

[0196] Data recording: Measure the mass difference before and after wear and record the amount of wear.

[0197] 3. Bonding strength test

[0198] Experimental procedures

[0199] Sample preparation: Prepare three samples per group for the bonding strength test.

[0200] Peel strength determination: Peel strength test was performed using a universal material testing machine.

[0201] Data recording: record the maximum peeling force and calculate the peeling strength.

[0202] The comparative experimental data are shown in Table 4:

[0203] Table 4 Comparative test results of different treatment methods for 12Cr2Mo1V steel forgings

[0204] Experiment Type Experimental Group Control group 1 Control group 2 Control group 3 Hardness (HV) 625 580 610 550 Wear amount (mg) 18 25 22 30 Peel strength (N / mm) 82 60 75 50

[0205] From the data in Table 4, we can get:

[0206] Hardness analysis:

[0207] The experimental group (cladding heat treatment) showed the highest average hardness value (625HV), which proved that the addition of cladding layer and subsequent heat treatment synergistically improved the hardness of the material. This is because the hard carbides (tungsten carbide and chromium carbide) in the cladding layer and the addition of titanium or nickel can form a more uniform and stable microstructure during the heat treatment process.

[0208] Although the hardness values ​​of control group 1 (cladding only) and control group 2 (heat treatment only) increased, they failed to reach the level of the experimental group, which shows that single cladding or heat treatment cannot fully stimulate the potential of the material.

[0209] The hardness of the control group 3 (untreated) was the lowest, which further proved the necessity and effectiveness of the treatment.

[0210] Wear resistance analysis:

[0211] The wear loss of the experimental group was the smallest (18 mg), indicating that the combination of cladding and heat treatment significantly enhanced the wear resistance of the material. Heat treatment helps to evenly distribute carbide particles and strengthen the interface, thereby improving the material's resistance to wear.

[0212] In contrast, the wear volume of control groups 1 and 2, although lower than that of the untreated samples, was higher than that of the experimental group, indicating that although a single treatment improved the condition, the effect was limited.

[0213] Control group 3 showed the highest wear, again emphasizing the importance of treatment in improving wear resistance.

[0214] Bond strength analysis:

[0215] The experimental group showed the highest peel strength (82N / mm), which indicates that the strongest bonding between the cladding layer and the substrate was achieved through cladding and heat treatment. This strong bonding is due to the diffusion and bonding of metal atoms at the interface during heat treatment and the optimization of the microstructure.

[0216] Although control group 1 and control group 2 showed a certain bonding strength, it was significantly lower than that of the experimental group, indicating that a single treatment could not fully achieve the optimal bonding of the material interface.

[0217] The bonding strength of control group 3 was the lowest, and the lack of any treatment resulted in insufficient bonding between the cladding layer and the substrate.

[0218] In general, the synergistic effect of cladding and heat treatment in Example 1 is significantly better than that of single treatment or untreated samples. This synergistic effect not only improves hardness and wear resistance, but also greatly enhances bonding strength, which is crucial for high-performance applications such as pressure vessels. Through this optimization treatment, the performance of 12Cr2Mo1V steel forgings has been comprehensively improved, fully demonstrating the effectiveness and practical value of the method of the present invention.

[0219] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A heat treatment process for 12Cr2Mo1V steel forgings for pressure vessels, characterized in that: The surface of the steel forging has a composite cladding layer, and the composite powder for preparing the composite cladding layer consists of 50%-70% tungsten carbide, 25%-40% chromium carbide and 5%-10% titanium or nickel; The particle size of the composite powder is 20-50 microns; The overlap rate between the layers of the composite cladding layer is 40%-60%; The preparation method of the composite cladding layer comprises the following steps: 1) Surface pretreatment, including cleaning and roughening; 2) Using laser surface cladding technology to form a composite cladding layer on the surface of the forging, the laser power is 1.5-2.5 kilowatts, and the scanning speed is 800-1200 mm / min; The roughening treatment in the surface pretreatment is completed by sandblasting or laser grinding, and the surface roughness is Ra 3.2-6.3 microns; The heat treatment process includes the following steps: After the composite cladding layer is prepared, it is subjected to preliminary heat treatment, with the tempering temperature at 250-350°C and the duration being 2-3 hours; Normalizing or quenching treatment, the normalizing temperature is 900-950℃, and the quenching temperature is 930-980℃; After normalizing or quenching, tempering is performed at a temperature of 500-650°C, and tempering is performed at least twice; After the initial heat treatment, cooling is performed at a cooling rate of 10-20°C / min; Normalizing or tempering after quenching lasts for 1-2 hours each time.

Citation Information

Patent Citations

  • Instrument with blade

    CN207581942U